1978
DOI: 10.1021/bi00605a017
|View full text |Cite
|
Sign up to set email alerts
|

Sites of phosphorylation on pyruvate dehydrogenase from bovine kidney and heart

Abstract: The highly purfied pyruvate dehydrogenase complex (EC 1.2.4.1) and uncomplexed pyruvate dehydrogenase from bovine kidney and heart mitochondria were phosphorylated and inactivated with pyruvate dehydrogenase kinase and [gamma-32P]ATP. Tryptic digestion of the phosphorylated pyruvate dehydrogenase yielded three phosphopeptides, a mono- (site 1) and a di- (sites 1 and 2) phosphorylated tetradecapeptide and a monophosphorylated nonapeptide (site 3). The amino acid sequences of the three phosphopeptides were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
173
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(186 citation statements)
references
References 23 publications
(26 reference statements)
11
173
1
1
Order By: Relevance
“…The two prominent polypeptides observed in lanes 1 and 2 are presumed to represent the Elc~ subunits of the pyruvate and branched-chain 2-oxo acid dehydrogenase multienzyme complexes (PDC and BCOADC). These radiolabelled components with Mr values 41,000 and 46,000, respectively, have been previously identified as the only two reversibly phosphorylated proteins known to be present in mammalian mitochondria [3][4][5]14]. Both PDC and BCOADC contain distinct intrinsic kinases which co-purify with the complexes, inactivating them in an ATP-dependent reaction.…”
Section: Profile Of Phosphoproteins In Rat Liver and Yeastmentioning
confidence: 97%
See 1 more Smart Citation
“…The two prominent polypeptides observed in lanes 1 and 2 are presumed to represent the Elc~ subunits of the pyruvate and branched-chain 2-oxo acid dehydrogenase multienzyme complexes (PDC and BCOADC). These radiolabelled components with Mr values 41,000 and 46,000, respectively, have been previously identified as the only two reversibly phosphorylated proteins known to be present in mammalian mitochondria [3][4][5]14]. Both PDC and BCOADC contain distinct intrinsic kinases which co-purify with the complexes, inactivating them in an ATP-dependent reaction.…”
Section: Profile Of Phosphoproteins In Rat Liver and Yeastmentioning
confidence: 97%
“…Phosphorylation by PDC kinase inactivates the complex, while dephosphorylation by a specific PDC phosphatase results in its reactivation. The phosphorylation sites in mammalian PDC are located on three particular serine residues in the ~ subunit of the pyruvate dehydrogenase (El) component of the complex [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these subunits (with the exception of E3BP) is involved in the conversion of pyruvate to acetylCoA in a stepwise manner. The complex is regulated largely via covalent modification by the addition of a phosphate group to at least one of its three serine residues located on the E1␣ subunit of the complex (15,31,33,34,37). Phosphorylation and inactivation are accomplished by a group of specific PDH kinases (PDK1-4), while dephosphorylation and activation are accomplished by a pair of PDH phosphatases (PDP1 and -2; Refs.…”
mentioning
confidence: 99%
“…Phosphorylation and inactivation are accomplished by a group of specific PDH kinases (PDK1-4), while dephosphorylation and activation are accomplished by a pair of PDH phosphatases (PDP1 and -2; Refs. 21,34,37). Each of these regulatory enzyme isoforms has different specificities and tissue expressions, with PDK2 and PDP1 being the most abundant isoforms in skeletal muscle (3,11).…”
mentioning
confidence: 99%
“…Phosphorylation occurs at 3 seryl residues (Ser-264, Ser-271, Ser-203) located on the c~ subunit. It has been shown that phosphorylation of Ser-264 closely is correlated with major inactivation of the enzyme [3,4].…”
Section: Introductionmentioning
confidence: 99%